Epidemiology of Bovine Trypanosomosis and its Economic Impact in Tsetse-Infested and Tsetse-Free Areas of Amhara Region, North-West Ethiopi - Asfaw, Thomas Cherenet (2004)
The epidemiology of bovine trypanosomosis was studied in tsetse-infested and tsetse-free areas of Amhara Regional State, North-West Ethiopia. A multidisciplinary work was undertaken to elucidate the key factors determining the presence of tsetse flies and magnitude of bovine trypanosomosis. Cattle were selected from tsetse-infested and tsetse-free areas for monthly monitoring of trypanosome infection by blood sampling on glass slides, dried blood spot and buffy coat spot on filter papers. In this study, parasitological, serological (Ab-ELISA) and PCR methods were used to characterize trypanosomes infecting the vector and the host. A total of 795 blood samples from cattle were examined from the tsetse-infested and tsetse-free areas; 13.5% of wet blood film and 15.6% of thin blood film were found positive for trypanosomes while PCR detected 18 % trypanosome infections. The dominant species was T.vivax, followed by T.congolense and T.brucei. T.vivax was higher in tsetse-free areas, whereas T.congolense was more in tsetse-infested areas, T.brucei and mixed infection of T.congolense and T.vivax were only present in tsetseinfested areas. The monthly trypanosome prevalence in tsetse-infested areas varied from 15 to 28% and in tsetse-free areas was 9 to 27%, with December having the highest prevalence in both study areas. Sera and dried blood spot on filter paper in Ab-ELISA showed strong correlation, providing for the use of the more convenient dried blood spot. In the retrospective study 7079 samples and accompanying data were analyzed for 5 consecutive years from the year 1997 till 2001. The prevalence of trypanosome infections was highest during the early dry season (September to December). Trypanosome infections were mainly due to T. vivax. Trypanosomosis reduced significantly the average packed cell volume and the body condition of the host. The monthly prevalence of infection was correlated with the density of biting flies suggesting their important role in transmission of trypanosomosis in the tsetse-infested and tsetse-free areas of the Amhara Region of north-west Ethiopia. Flies were trapped for 3 days each month in the study period using 4 types of traps (`Biconical’, `NGU’, `Pyramidal’ and hand net). A total of 5652 tsetse and other biting flies were captured; 3532 flies from tsetse-infested areas and 2120 flies from tsetse-free areas. PCR amplification analyses for trypanosome identification were carried out on 3751 flies, with primer sets specific for Trypanosoma (Duttonella) vivax, T. (Nannomonas) congolense and T. (Trypanozoon) brucei. Of 3751 flies; 699 (18.64%) were positive in PCR analysis with 132 (12.13 %) from tsetse-free areas and 567 (21.29